STRATEGI KEBERHASILAN KEGIATAN REHABILITASI PADA DAERAH ALIRAN SUNGAI KAPUAS DI KABUPATEN KAPUAS - Nugroho, Bayu; Achmad, Basir; Kadir, Syarifuddin (Jurnal Hutan Tropis, 2024)
In overcoming the problem of critical land and watershed degradation, the government has launched Forest and Land Rehabilitation activities, abbreviated as RHL, in an effort to restore, maintain and improve the function of forests and land to improve their their carrying capacity, productivity and role in maintaining life support systems (PP 26 of 2020 on Rehabilitation and Reclamation). The Kapuas watershed is no exception, which contains protected forests, especially in Mantangai District in Katunjung Village, Sei Ahas Village, and Katimpun Village, where the area consists of peat swamp forest. The aim of this research is to describe the research area, community involvement (participation) in the Kapuas watershed, namely in Katunjung Village, Sei Ahas Village, and Katimpun Village. Formulate a strategy for community involvement in the success of watershed rehabilitation. The results of the analysis show that for Katunjung Village the values of the application of the strategy in quadrant II is a diversification strategy, that is, even though there are outstanding challenges, there are internal strengths that can be developed into breakthroughs and optimized to overcome challenging factors that are also quite strong. Meanwhile, for Ketimpun village, the strategic position is in quadrant IV with the respective X and Y values being (X= -0.5; Y= -0.486). The strategy in quadrant IV is a defensive strategy. In this quadrant, the implementation of rehabilitation experiences enormous challenges with weaknesses that are also very influential, so it is necessary to overhaul existing strategies.